METHODICAL TEACHING SYSTEM SOLVING TASKS - Skvortsova, S.O. (Pedagogy of Higher and Secondary Education, 2022)
In the article of Skvortsovoy Svetlany “Methodical system of studies of untiing of tasks”. The aims of with plots tasks are certain in a course mathematics of primary school, maintenance of task material and programmatic minimum is shortly described certain the basic method of studies of untiing of tasks, as the special systems of educational tasks, organizational forms and facilities of studies are reflected, among which a certain place belongs to the design as text of task so process of its untiing.